2019
DOI: 10.1155/2019/8057820
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Detection by the Combination of Recurrence Complex Network and Convolution Neural Network

Abstract: In this paper, R wave peak interval independent atrial fibrillation detection algorithm is proposed based on the analysis of the synchronization feature of the electrocardiogram signal by a deep neural network. Firstly, the synchronization feature of each heartbeat of the electrocardiogram signal is constructed by a Recurrence Complex Network. Then, a convolution neural network is used to detect atrial fibrillation by analyzing the eigenvalues of the Recurrence Complex Network. Finally, a voting algorithm is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It can be seen that the proposed lightweight CNN tends to outperform those algorithms without considerations of cardiac rhythms. Wei et al [38] achieved an accuracy of 94.59% for AF detection by using a CNN based classifier with initial features of recurrence complex network, while a longer training time of 9.65 h is needed for this 6-layer CNN. Meanwhile, Xu et al [39] and Xia et al [28] reported two CNN based detectors with more than 10 layers with an accuracy of 84.5% and 98.63%, respectively.…”
Section: Discussion a Higher Performance Comparing To Existing mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the proposed lightweight CNN tends to outperform those algorithms without considerations of cardiac rhythms. Wei et al [38] achieved an accuracy of 94.59% for AF detection by using a CNN based classifier with initial features of recurrence complex network, while a longer training time of 9.65 h is needed for this 6-layer CNN. Meanwhile, Xu et al [39] and Xia et al [28] reported two CNN based detectors with more than 10 layers with an accuracy of 84.5% and 98.63%, respectively.…”
Section: Discussion a Higher Performance Comparing To Existing mentioning
confidence: 99%
“…However, the training process can be carried out off-line. In this work, the proposed lightweight CNNs by using two cardiac rhythm features as input can be trained in less than 10 minutes to converge with 2,000 back propagation iteration, and the training time is also less than others previous works [28], [38], [40], as shown in Table 4. Two of the important reasons that we used less time for training possibly include there two initially extracted representative rhythm features and a lightweight CNN model, which both could speed up the deep learning of hidden features and obtain a faster training of our proposed model.…”
Section: B Real-time Identification Of Af With Lower Computational Costmentioning
confidence: 98%
See 1 more Smart Citation
“…The effective analysis of ECG signals is helpful to detect many heart diseases such as atrial fibrillation (AF), myocardial infarction (MI), and heart failure (HF) ( Turakhia, 2018 ). In an AF waveform, the P wave is replaced by many inconsistent fibrillatory waves, and the RR interval is irregular, which is easily mixed with other diseases ( Wei et al, 2017 ). In the early stage, the research work of ECG classification was generally implemented by using manual feature extraction method.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], different kinds of arrhythmia have been classified by employing an ANN based technique which exploits morphological and dynamic features. The classification of different categories of cardiac arrhythmias has also attracted the use of advanced ANN based algorithms such as Deep Neural Networks [9 -10], Deep Convolutional Neural Networks (CNN) [11], hybridization of CNN and Recurrence Complex Networks [12], etc. The use of a hybrid approach combining learning approaches like the deep/ensemble learning, and evolutionary optimization techniques to enhance the accuracy of arrhythmia detection has been recently reported by [13].…”
Section: Introductionmentioning
confidence: 99%